Epidemiological trends and risk factors of CKD-T1DM in children and adolescents across 204 countries and territories (1990–2021) - Liu, Beiyan; Li, Fengrui; Cui, Huanxi; Li, Lin; Ma, Ying; Yang, Qizhi; Cui, Ying (Frontiers in Endocrinology, 2025)
BackgroundGlobal T1DM incidence in children and adolescents is rising, leading to Chronic Kidney Disease due to Type 1 Diabetes Mellitus (CKD-T1DM), a critical public health concern. Severe cases evolve into end-stage kidney disease (ESKD), requiring dialysis or transplantation, severely impacting quality of life and imposing substantial burdens.MethodsThis study used Global Burden of Disease (GBD) data to analyze global and regional CKD-T1DM incidence, prevalence, mortality, and Disability-Adjusted Life Years (DALYs) rates in children and adolescents (1990-2021). It calculated age-standardized ratios and estimated annual percentage change (EAPC), presenting findings via maps and comparing age-specific burdens and mortality patterns.FindingsFrom 1990 to 2021, CKD-T1DM prevalence and incidence in children and adolescents increased globally, while mortality and DALYs declined. Middle SDI (Socio-Demographic Index) nations saw a surge in new cases, contrasting with High SDI countries’ success in reducing DALYs. Male incidence and DALYs were higher than those of females, with notable rises in Eastern Europe, Central Latin America, and Central Europe, and drops in East Asia. The 10-14 age group exhibited higher incidence, and the 15-19 age group higher DALYs.InterpretationGlobal CKD-T1DM management in children and adolescents faces challenges. Future research should focus on SDI-specific needs, resource allocation, public awareness, and community health education. Early detection and comprehensive health protection are crucial, especially in middle and low SDI countries and high-incidence areas.